Enhancing Students' Vocabulary Ability Through Matching Picture By Word - Amiruddin, Amiruddin; Satriani, Satriani (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The goal of the study was to see if using matching photos by word may help students improve their vocabulary in the second semester of IAI As'adiyah Sengkang. This study used a one-group pre-test and post-test design with a pre-experimental approach. The study's participants were IAI As'adiyah Sengkang students in their second semester. A total of 13 English education students were included in the study. The value of significance of 0.00, which was lower than the level of significance (a) = 0.05, was used to prove the data of the students' vocabulary capacity, which was obtained through the usage of matching pictures by word at the vocabulary test. The post-mean test's score (75.41) was higher than the pre-mean test's score (25.00). The researcher concluded, based on the findings and discussion of the study, that employing matching pictures by word improved the students' vocabulary skills in the second semester of IAI As'adiyah Sengkang.